2020
DOI: 10.25176/rfmh.v20i3.3054
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with suicide ideation in patients of a Peruvian Hospital

Abstract: un artículo de acceso abierto, distribuído bajo los términos de la Licencia Creative Commons: Creative Commons Attribution 4.0 International, CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/), que permite el uso no comercial, distribución y reproducción en cualquier medio, siempre que la obra original sea debidamente citada. Para uso comercial, por favor póngase en contacto con

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…No signi cant gender-related SI data were reported (9). In Peru, a study revealed a female predominance in its sample, married or cohabiting individuals (68.2%), with a higher prevalence of SI in patients with a secondary education or higher and in young hospitalized patients (34).…”
Section: Discussionmentioning
confidence: 95%
“…No signi cant gender-related SI data were reported (9). In Peru, a study revealed a female predominance in its sample, married or cohabiting individuals (68.2%), with a higher prevalence of SI in patients with a secondary education or higher and in young hospitalized patients (34).…”
Section: Discussionmentioning
confidence: 95%
“…The Scale for Suicide Ideation -Worst (SSI-W) is a 19-item instrument, with each item having three response options (0 to 2 points), which suggest an increasing level of risk, seriousness, and intensity of suicidal behavior (Beck et al, 1979). BIS has optimal reliability values in the overall dimension (α=0.79) (Eugenio Torres & Zelada Alcántara, 2011) and has been used in studies in the Peruvian context (Chavez-Cáceres et al, 2020). We dichotomized the presence of suicidal ideation based on scores ≥14 (Beck et al, 1999).…”
Section: Suicidal Ideationmentioning
confidence: 99%